Biogerontology: research status, challenges and opportunities - Rattan, Suresh I.S. (Acta Biomedica Atenei Parmensis, 2018)
Biogerontology is the study of the biological basis of ageing and age-related diseases. The phenomenon and the process of ageing are well understood in evolutionary and biological terms; and a conceptual framework has been established within which general principles of ageing and longevity can be formulated. The phenotype of ageing in terms of progressive loss of physical function and fitness is best seen during the period of survival after the evolution-determined essential lifespan (ELS) of a species. However, the ageing phenotype is highly heterogenous and individualistic at all levels from the whole body to the molecular one. Most significantly, the process and the progression of ageing are not determined by any specific gerontogenes. Ageing is the result of imperfect maintenance and repair systems that allow a progressive shrinkage of the homeodynamic space of an individual. The challenge is to develop and apply wholistic approaches to the complex trait of ageing for maintaining and/or improving health. One such approach is that of mild stress-induced physiological hormesis by physical, mental and nutritional hormetins. Biogerontological research offers numerous opportunities for developing evidence-based novel biomedical technologies for maintaining and improving health, for preventing the onset of age-related diseases, and for extending the health-span.